Exposure–Response Modeling and Simulation of Progression‐Free Survival and Adverse Events of Sorafenib Treatment in Patients With Advanced Thyroid Cancer. Issue 5 (12th April 2019) - Grevel, Joachim; Jentsch, Garrit; Austin, Rupert; Prins, Nicolaas H.; Lettieri, John; Mitchell, David; Huang, Funan; Brose, Marcia S.; Schlumberger, Martin; Meinhardt, Gerold; Peña, Carol E. A.; Ploeger, Bart A.
Abstract : Sorafenib is an oral multikinase inhibitor approved for the treatment of differentiated thyroid carcinoma (DTC), renal cell carcinoma, and hepatocellular carcinoma. In the phase III DECISION trial in patients with DTC, sorafenib exposure and the incidence of some adverse events (AEs) were higher than in previous trials; therefore, we analyzed exposure–response relationships, including progression‐free survival (PFS) and selected AEs in patients with DTC. A novel, stratified prediction‐corrected visual predictive check (pc‐VPC) was developed to show robustness of the exposure–response relationships. Time‐to‐event simulations confirmed the benefit of the recommended dosing schedule of 800 mg/day: initial doses of 800 mg/day were associated with the highest PFS, whereas lower doses (600 or 400 mg/day) were associated with improved tolerability but reduced PFS. A simulated dose‐reduction strategy of 800 mg/day for an initial two cycles followed by dose reductions seemed likely to maintain efficacy while possibly mitigating selected AEs (e.g., diarrhea and hand‐foot skin reactions).